(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:The current research aims to identify the use of manufactured materials in organizing the surface of the murals.The researcher adopted the analytical descriptive approach because it is the most appropriate with the directions of the current research, and a community of graphic artistic productions implemented on the walls of the educational institution, amounting to (35) artistic productions, was identified, and one model was chosen as a sample for the research for the purpose of subjecting it to the analysis process and according to the indicators of the theoretical framework:The most important results are:2- There were many stimuli in the art of drawing murals represented in the concepts of popular culture, speed and spontaneity as in the sample.3- Its stimuli carried meaning, interpretation, and the diversity of connotations, and relied on employing the concepts of mosaic art.Keywords: Employment - materials - mural art